(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
The development of the oil industry in the last decade is characterized by the discovery of new fields and increased production rates from old ones. Among the researchers and production specialists are the problems of using complex structural oil and gas dumps, viscous and highly viscous carbonate reservoirs and their solutions. The structure, geological physical characteristics, and saturation properties of such deposits with such fluids make extraction difficult.